2012
DOI: 10.3319/tao.2011.11.14.01(aa)
|View full text |Cite
|
Sign up to set email alerts
|

Seismo-Tsunamigenic Ionospheric Hole Triggered by M 9.0 2011 off the Pacific Coast of Tohoku Earthquake

Abstract: Giant earthquake and tsunami widely disturbed ionospheric plasma via acoustic gravity waves. During the M 9.0 2011 off the Pacific coast of Tohoku earthquake, the ionospheric disturbances were generated by co-seismic epicentral ground/sea surface motion, Rayleigh-wave traveling, and tsunami-wave traveling. In addition, seismo-tsunamigenic ionospheric hole, widely sudden depression of ionospheric total electron content, was observed. The ionospheric hole gradually disappeared within roughly a few tens minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…From the propagation velocities and periods of the VTEC oscillations shown in Table 1, two types of short period ionospheric disturbances were observed. The first type of ionospheric disturbance observed at stations nearer to the epicenter (0214, 0202 and 0191) has high amplitudes and average propagation velocity of 1212 m/s, which is in close agreement with the velocities (~1 km/s) observed by [6,8,12] for the same study area and the previous study [1] [3]. It is suggested that the VTEC oscillations of type 1 are caused by the collision interaction of the acoustic waves in the neutral atmosphere that are induced by the sudden uplift of the sea surface and charged particles in the ionosphere above the altitude of 100 km [13].…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…From the propagation velocities and periods of the VTEC oscillations shown in Table 1, two types of short period ionospheric disturbances were observed. The first type of ionospheric disturbance observed at stations nearer to the epicenter (0214, 0202 and 0191) has high amplitudes and average propagation velocity of 1212 m/s, which is in close agreement with the velocities (~1 km/s) observed by [6,8,12] for the same study area and the previous study [1] [3]. It is suggested that the VTEC oscillations of type 1 are caused by the collision interaction of the acoustic waves in the neutral atmosphere that are induced by the sudden uplift of the sea surface and charged particles in the ionosphere above the altitude of 100 km [13].…”
Section: Methodssupporting
confidence: 85%
“…The previous study for the same event [6] observed that there are depressions for about 5 TECU and lasted after 40 minutes southwest from the epicenter but such long depression were not observed in the northeast direction as shown earlier in our result. While another study [12] have shown the direction is in northwestward.…”
Section: Methodscontrasting
confidence: 69%
See 1 more Smart Citation
“…Besides traveling ionospheric disturbances generated by an epicentral ground/sea surface motion, ionospheric disturbances associated with Rayleigh‐waves as well as post‐seismic 4‐minutes monoperiodic atmospheric resonances and other‐period atmospheric oscillations [ Saito et al , 2011; Tsugawa et al , 2011; Rolland et al , 2011; Kamogawa et al , 2012], the ionospheric hole appears due to the tsunami induced by the subduction EQs. The tsunamigenic ionospheric hole is caused by the meter‐scale downwelling of the sea surface at the tsunami source area yields the hundred‐kilometer‐scale ionospheric plasma downwelling and plasma depletion due to the high recombination of plasma at the lower thermosphere through the chemical processes.…”
Section: Resultsmentioning
confidence: 99%
“…These data were obtained at Japan, Taiwan, and South Korea. The frequency of ionospheric disturbance seen in TEC variation in this event was slower than those observed after earthquakes [e.g., Calais and Bernard Minster, 1995;Choosakul et al, 2009;Kamogawa et al, 2012;Kakinami et al, 2013]. In the figure, the ionospheric point (IP) where the raypath from the GPS satellite pierced the ionosphere was assumed to be 425 km.…”
Section: Data and Analysismentioning
confidence: 99%